Rehearsing for the future: play, place and art. Issue 2 (3rd April 2021) - Luostarinen, Nina; Schrag, Anthony
ABSTRACT: This paper explores the confluence of art, play and places, presenting three case studies enacted via participatory art projects which asked: How can artistic play change our relationship to place? The research was practice-based via participatory art and presents new, ludic cultural practices in regards to art, play and place. The case studies discuss how participants became liberated from normal adult behaviour in public spaces because of the alibi of art and play, as well as enjoying and interacting with the place differently. The artworks were contextually responsive to the specificities of each place, allowing players an opportunity to develop new, positive place-relationships. It also includes a reflection on the political imperatives of play in assisting adults imagining new futures for themselves. The findings of this paper are useful to those involved in heritage or cultural projects seeking to develop new audience relationships with their specific places. HIGHLIGHTS Adult play can be considered a 'rebel base for imagination' that helps with audience development for heritage/cultural projects. Framing 'play' as an 'artistic process' encourages deeper engagement from adults, and this more effective engagement with place. Conflict-based play approaches allows the politics of plurality and dissensus to occur and as such, is more age-appropriate for adults because such work involves complex themes responding to specific localities. Play gives an opportunity for adults to 'rehearse our future' in regards to politics, culture and place, enabling capacity to explore meaning within our lives